2019
DOI: 10.1155/2019/2083196
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Associated Factors among Diabetic Patients in an Outpatient Diabetes Clinic

Abstract: Despite adequate treatment for diabetes, it is estimated that 15%- 20% of people with diabetes are struggling with a moderate to severe form of depression daily. Little is known about depression in diabetes in East Africa, particularly in Tanzania. The study is aimed at determining the prevalence of depression and associated factors among patients with diabetes. A descriptive cross-sectional study was carried out at the diabetes clinic of Muhimbili National Hospital. The 9-item Patient Health Questionnaire (PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 18 publications
6
24
2
10
Order By: Relevance
“…This magnitude is almost similar to the findings of studies conducted in Malaysia (40.3%) [31], Southern India (37.5%) [34], and Nepal (34%) [35]. However, the finding is lower than studies conducted in Ethiopia, 43.6% [36], and Tanzania (87%) [17]. The inconsistency between the current and former studies might be due to variation in the tools used to measure depression, sociocultural, and behavioral-related factors among study participants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This magnitude is almost similar to the findings of studies conducted in Malaysia (40.3%) [31], Southern India (37.5%) [34], and Nepal (34%) [35]. However, the finding is lower than studies conducted in Ethiopia, 43.6% [36], and Tanzania (87%) [17]. The inconsistency between the current and former studies might be due to variation in the tools used to measure depression, sociocultural, and behavioral-related factors among study participants.…”
Section: Discussionsupporting
confidence: 87%
“…The occurrence of depression in people with diabetes mellitus is about two to three times higher compared to the general population [11][12][13]. Studies have reported varying results on the prevalence of depression in diabetes patients that ranges from 5.9% to 87% [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Sebanyak 87% penderita diabetes melitus mengalami depresi. (Khan, Lutale, & Moledina, 2019). Penelitian Vuuren & Pillay, (2019) mengungkapkan sebanyak 46,6% penderita diabetes melitus mengalami gangguan depresi mayor.…”
Section: Depresiunclassified
“…Sementara hasil penelitian (Wang, Lopez, Bolge, Zhu, & Stang, 2016) mengungkapkan bahwa kejadian depresi yang relevan secara klinis pada penderita diabetes melitus sebesar 10,6% dan depresi signifikan secara klinis sebesar 4,2%. Data ini menggambarkan bahwa penderita diabetes melitus memiliki resiko tinggi mengalami depresi Depresi pada penderita diabetes dapat disebabkan oleh faktor genetik, biologis dan psikologis (Niraula, Kohrt, Flora et al, 2013;Khan et al, 2019) Menurut Holt, de Groot, & Golden (2015), mekanisme dan patogenesis yang mendasari hubungan antara depresi dengan diabetes melitus adalah beban klinis dari penyakit, faktor gaya hidup dan kepatuhan, obat antidepresan, struktur dan fungsi otak, disfungsi aksis HPA, gangguan tidur, peradangan, dan faktor lingkungan. Holt et al (2015) mengungkapkan depresi pada klien diabetes melitus cenderung disebabkan oleh pengetahuan terhadap diagnosis, beban mengelola kondisi dan komplikasi penyakit.…”
Section: Depresiunclassified
“…The wide range of reported prevalence estimates may be due to differences in assessment tools and variation in the types of patients in the studies cohorts. Depression in patients with diabetes is often associated with poor glycaemic control, poor adherence to medication, and rapid development of complications (5)(6)(7). Furthermore, depression is often undiagnosed and untreated in this patient population (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%